No Pain Management for Labor: Individual and Organizational Determinants: A Secondary Analysis of the 2016 French National Perinatal Survey. Issue 1 (22nd March 2023) - Merrer, J.; Chantry, A.A.; Blondel, B.; Le Ray, C.; Bonnet, M.P.
Abstract : ( Eur J Anaesthesiol . 2022;39:489–497) Pain management during labor and delivery is a fundamental right for patients in labor. Disparities in women's access to analgesia in childbirth requires further research. Using national data, this study aims to determine the proportion of women who receive no labor pain management, and its individual and organizational factors.